Syntactic constructions and pragmatic values of the French pronoun on. A contrastive study based upon a specific Franco-Spanish corpus - Chovancová - Lucia Ráčková - Eva Reichwalderová, Katarína (Romanica Olomucensia, 2022)
The problem presented here consists of a comparative French-Spanish study based on a literary corpus, the novel in French by Patrick Modiano Souvenirs dormants and its corresponding Spanish translation Recuerdos durmientes. The research focuses on the French pronoun on. This replaces the animated generic subject, either as a personal pronoun or as an indefinite pronoun. In Spanish, it does not have a semantic and structural equivalent and that is why on is translated into se constructions, non-reflexive forms, or uno forms. As on is an ambiguous and polysemic element of grammar, rich in deictic, anaphoric, and presentative values, after the occurrences of on and its function in the French corpus have been located, it will be put into a relationship with its values and their equivalents and constructions identified in the Spanish Modiano corpus. The main findings resulting from the examination of this parallel corpus are the following: a) the use of non-reflexive constructions with a generic subject is predominant in the Spanish version of the contemporary novel, mainly in statements of anaphoric value, especially when the latter is strict; b) reflexivity does not play a distinctive role in the research for functional equivalence in the data that was analysed. This article aims to contribute to the contrastive research of constructions with the French on and the different ways of expressing it in Spanish. Applications of the results of the research could be expected in French-Spanish and Spanish-French translations, in particular concerning the imperative respect of the meaning conveyed by the literary text.
Keywords: Souvenirs dormants; Patrick Modiano; values of the pronoun on; functional equivalence; se constructions; French-Spanish contrastive study